The National Archives of Nigeria and the Management of Public Records: A Proposed Repositioning Model Based on Digital Age Requirements - AUYO, MUSA ABDU; MAIDABINO, A. A. (MiddleBelt Journal of Library and Information Science, 2020)
Information and Communication Technologies (ICTs) have permeates all facets of human life including the generation/creation, receiving, transfer, use and management of public records. Public records are records created by public institutions. Such records can be used by individuals, organizations, and as well for societal development. The National Archives of Nigeria is mandated by law to ensure proper acquisition and management of records created and maintained by public institutions or bodies within and outside the country. This paper examines the concept of records and archives and their significance for societal development. The management practices involved in the custody and care of national records have also been highlighted. The paper also describes the statutory mandate of the Nigerian National Archives and how the institution can be repositioning in line with the digital age requirements. The paper concludes by proposing a model for the management of National Archival Institutions for effective records and archival management. The model emanates from the critical analysis of the existing body of knowledge. It is hope that the proposed model will assist stakeholders through serving as a guiding tool for effective management of public records in the National Archival Institutions in Nigeria and beyond.